The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/genes11091051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diagnostic Biomarkers and Subtypes of Liver Hepatocellular Carcinoma by Multi-Omics Data Analysis

Abstract: As liver hepatocellular carcinoma (LIHC) has high morbidity and mortality rates, improving the clinical diagnosis and treatment of LIHC is an important issue. The advent of the era of precision medicine provides us with new opportunities to cure cancers, including the accumulation of multi-omics data of cancers. Here, we proposed an integration method that involved the Fisher ratio, Spearman correlation coefficient, classified information index, and an ensemble of decision trees (DTs) for biomarker identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 66 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…There is a significant morbidity and death rates associated with liver hepatocellular carcinoma (LIHC), therefore improving clinical diagnosis and treatment of LIHC is important [45]. Several additional research have reported on the use of gene expression data to find LIHC biomarkers [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant morbidity and death rates associated with liver hepatocellular carcinoma (LIHC), therefore improving clinical diagnosis and treatment of LIHC is important [45]. Several additional research have reported on the use of gene expression data to find LIHC biomarkers [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on GABRD have focused on neurological diseases, and several studies have recently revealed the possible functional role of GABRD in tumors. Studies based on genomics datasets including mRNA expression data from The Cancer Genome Atlas (TCGA) database showed that GABRD expression was associated with corticotrophinomas, hepatocellular carcinoma, kidney renal clear cell carcinoma, thyroid carcinoma and other tumors, which indicated that GABRD might 4 serve as a potential biomarker to predict patient prognoses (6)(7)(8). However, little is known about the involvement of GABRD in the tumorigenesis and progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in addition to traditional methods including liver transplantation, sorafenib, and other available treatments for LIHC, 3 many combination methods including combinations of different immune checkpoint inhibitors (ICIs) are under investigation 4,5 . For prognostic prediction of patients with LIHC, the patient's physical status, degree of liver dysfunction, tumor expansion, and alpha‐fetoprotein (AFP) concentration are the main factors 6,7 . Therefore, the identification and comprehensive analysis of novel molecular biomarkers will benefit the ability to predict patient prognosis in LIHC.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 For prognostic prediction of patients with LIHC, the patient's physical status, degree of liver dysfunction, tumor expansion, and alpha‐fetoprotein (AFP) concentration are the main factors. 6 , 7 Therefore, the identification and comprehensive analysis of novel molecular biomarkers will benefit the ability to predict patient prognosis in LIHC.…”
Section: Introductionmentioning
confidence: 99%